Endodontic treatment regimens and their application in practice - survey and comparative study - Łucja Kula (Journal of Education, Health and Sport, 2021)
Introduction: Endodontics is a rapidly developing field of dentistry. Dentists have an increasing selection of techniques, tools, and materials to ensure therapeutic success. Aim: The aim of the study was to analyze the endodontic treatment regimens and their application in the daily practice of dentists.  Material and Methods: A dentist survey was conducted through a Google Doc. The link to the form was placed on online dental groups, sent by e-mail to the offices and the questionnaire was also delivered to the dental offices in a printed form. Results: The majority of respondents always perform endodontic treatment procedures on pregnant women, take three X-rays and use a rubber dam during the treatment. Almost all respondents have the opportunity to take an X-ray in the workplace, and the working length is usually measured by the electronic method. The most commonly used methods of root canal preparation are the traditional and crown-down methods, and the most commonly used root canal filling method - the thermal method. Most of the respondents declared the following rinsing protocol: NaOCl and CA or EDTA.  Apex locator, ultrasounds, and microscopes are used in most dental offices, and more than half of the dentists responded that they perform procedures like broken tools removal or obliterated canals enlargement. Conclusions: Polish endodontics has developed over the years. Modern solutions are used more and more often. The canals are filled with the thermal method, and the popularity of performing complex endodontic procedures has increased. However, it is necessary to conduct further studies comparing the effectiveness of the canal preparation methods and the standardization of the root canal irrigation protocol.